Riesgos psicosociales en el desempeño laboral de los servidores públicos y auxiliares de servicio de la fiscalía de la provincia de Morona Santiago, en el cuarto trimestre del año 2014. - Flores Camas, Rosa Alva (2016)
This research has notability on function that psychosocial risks have been influenced by the Fiscally of Morona Santiago province; the problematic was to determine how psychosocial risks affect job performance of public servants and service assistants. The general objective is to determine the psychosocial risks in the job performance of public servants and service assistants. Deductive-inductive methods were used for this research work, the casual relationship was considered, it is based on general facts to reach particular situations. Also, Analytic – Synthetic methods were used; it was considered that draw from the breakdown of each one of its parts to study them individually and then in a holistic and comprehensive was considered, in this case the psychosocial risks at job performance to reach the objectives. The Research design is of field, on scene of the events has been obtained the information. The survey was conducted at the public servants and service assistants on scene of the events, in order to obtain their views on the topic investigated and fulfill the objectives. It can be evidenced that the psychosocial risks if they influence job performance of workers. The research is descriptive and explanatory; whose populations were 53 public servants and service assistants from Fiscally of Morona Santiago province. Finally, the main conclusion is that, it was related to the problem of psychosocial risks is one of the main causes of low job performance of public servants and service assistants, because in the correct job performance includes a good emotional and cognitive stability. The psychosocial risks are aspects, which affect the physical and mental health of workers, resulting in poor management of emotional intelligence and thereby family problems. The main recommendation is to propose programs on emotional stability in job performance, which allows taking for natural and positive attitudes to the facts related to job occupation.